Lichen Polyphenolic Compounds for the Eradication of Candida albicans Biofilms - Girardot, Marion; Millot, Marion; Hamion, Guillaume; Billard, Jeanne-Louise; Juin, Camille; Ntoutoume, G M A Ndong; Sol, Vincent; Mambu, Lengo; Imbert, Christine (Frontiers in Cellular and Infection Microbiology, 2021)
Lichens, due to their symbiotic nature (association between fungi and algae), constitute a chemical factory of original compounds. Polyphenolic compounds (depsides and depsidones) are the main constituents of lichens and are exclusively biosynthesized by these organisms. A panel of 11 polyphenols was evaluated for their anti-biofilm activity against Candida albicans biofilms on the maturation phase (anti-maturation) (MMIC50) as well as on preformed 24-h-old biofilm (anti-biofilm) (MBIC50) using the XTT assay. Minimum inhibitory concentrations of compounds (MICs) against C. albicans planktonic yeast were also determined using a broth microdilution method. While none of the tested compounds were active against planktonic cells (IC50 > 100 µg/ml), three depsides slowed the biofilm maturation (MMIC50 ≤12.5 µg/ml after 48 h of contact with Candida cells). Evernic acid was able to both slow the maturation and reduce the already formed biofilms with MBIC50 ≤12.5 µg/ml after 48 h of contact with the biofilm. This compound shows a weak toxicity against HeLa cells (22%) at the minimal active concentration and no hemolytic activity at 100 µg/ml. Microscopic observations of evernic acid and optimization of its solubility were performed to further study this compound. This work confirmed the anti-biofilm potential of depsides, especially evernic acid, and allows to establish the structure–activity relationships to better explain the anti-biofilm potential of these compounds.